2022
DOI: 10.3390/f13071124
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for In Vitro Propagation of Salix acmophylla (Boiss.). Studies on Three Ecotypes

Abstract: Salix acmophylla Boiss. has a traditional role in several regions of the Middle East and the Indian subcontinent. As with many other woody species, the development of methods for fast propagation and ex situ conservation of this species is needed. We describe for the first time a micropropagation protocol of three S. acmophylla ecotypes. The best results for shoot proliferation were obtained by culturing the shoot explants on Woody Plant Medium (WPM) containing benzyladenine (BA) 5 μM, but it was also observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
(72 reference statements)
0
0
0
2
Order By: Relevance
“…In particular, according to L.K. Simola (1985) it was found that peat humic substrate is optimal for the survival of B. pendula plants; according to N. Dimitrova et al (2021) for P. communis plants, it is -peat-perlite substrate; according to M. Capuana et al (2022) for S. acmophylla -a mixture of garden soil, peat, and sand; according to S. Välimäki et al (2021) for U. laevis and U. glabra -light sphagnum peat. According to the results of this study, it is advisable to adapt Betula ex vitro hybrid plants on an agroperlite substrate (over 60% survival rate).…”
Section: Table 3 Characteristics Of Plant Growth Of Hybrid Betula Ex ...mentioning
confidence: 99%
“…In particular, according to L.K. Simola (1985) it was found that peat humic substrate is optimal for the survival of B. pendula plants; according to N. Dimitrova et al (2021) for P. communis plants, it is -peat-perlite substrate; according to M. Capuana et al (2022) for S. acmophylla -a mixture of garden soil, peat, and sand; according to S. Välimäki et al (2021) for U. laevis and U. glabra -light sphagnum peat. According to the results of this study, it is advisable to adapt Betula ex vitro hybrid plants on an agroperlite substrate (over 60% survival rate).…”
Section: Table 3 Characteristics Of Plant Growth Of Hybrid Betula Ex ...mentioning
confidence: 99%
“…Las mismas se oxidaron y necrosaron. Esto difiere de los resultados obtenidos por Capuana et al (2022) que ajustaron un protocolo de micropropagación de tres ecotipos de S. acmophylla, a partir de yemas en un medio que contiene BA o carbón activado y Xiaoxia et al (2020) que obtuvieron plantas de S. matsudana desde yemas apicales en un medio WPM suplementado con Zeatina y ANA. Si bien el explante más usado para los procesos de propagación in vitro son las yemas vegetativas de las plantas, siendo éstas las que mejor garantizan la clonación, en este trabajo no se pudo optimizar un protocolo de regeneración a partir de este tipo de explante.…”
Section: Micropropagación De Salix Hu Mb Oldt Ian Aunclassified
“…La micropropagación (organogénesis directa e indirecta y embriogénesis somática) es una herramienta adecuada para facilitar la multiplicación de genotipos de sauce seleccionados por diferentes rasgos deseados como su capacidad fitorremediadora, para conservar germoplasma o simplemente para contar con una gran cantidad de individuos para reintroducir en paisajes degradados o contaminados. Varios autores han reportado métodos exitosos de micropropagación para diferentes especies de sauces (Lyyra et al, 2006;Naujoks, 2007;Paek et al, 2008;Mashkina et al, 2010;Capuana et al, 2022). La literatura cita una amplia gama de variantes de medios de cultivo con diferentes composiciones de nutrientes básicos y fitohormonas.…”
Section: Introduccionunclassified